2019
DOI: 10.21203/rs.2.432/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biometric indicators of Eyes with Occult Lens Subluxation inducing Secondary Acute Angle Closure

Abstract: Background: To compare the anterior biometry of eyes with secondary acute angle closure induced by occult lens subluxation (LS), misdiagnosed as acute primary angle closure (APAC) at the first visit, APAC, chronic primary angle closure glaucoma (CPACG), cataract. Methods: This retrospective case study included 17 eyes with PAC due to occult LS, who were misdiagnosed as APAC on their first visit, 56 eyes diagnosed as APAC, 54 eyes diagnosed as CPACG, and 56 eyes diagnosed as cataract. Axial length (AL), Central… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Lens subluxation is a multifactorial disease, with symptoms that can be variable and occult [7,8]. In the present study, we analyzed clinical characteristics and multimodal biometric parameters of patients with ASAC-LS, APAC, and cataract obtained from UBM and the IOL Epidemiological studies have shown that the prevalence of PACG is highest in East Asia [1,6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lens subluxation is a multifactorial disease, with symptoms that can be variable and occult [7,8]. In the present study, we analyzed clinical characteristics and multimodal biometric parameters of patients with ASAC-LS, APAC, and cataract obtained from UBM and the IOL Epidemiological studies have shown that the prevalence of PACG is highest in East Asia [1,6].…”
Section: Discussionmentioning
confidence: 99%
“…The medical records of patients with ASAC-LS, APAC, and cataract attending the two hospitals from September 2019 to February 2022 were consecutively reviewed. We applied the following inclusion criteria of ASAC-LS [7,8]:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The AL to corneal radius (AL/CR) ratio was computed with both AL and CR expressed in millimetres. Corrected lens position (LP) is defined as the sum of the AQD and half of the LT (Xing et al 2020). The calculation of the lens power (P Bennett ) was based on the formula proposed by Bennett, (Bennett 1988; Rozema et al 2011) with A and B constants extracted from the Gullstrand–Emsley eye model, where the lens refractive index was set to be n L = 1.416.…”
Section: Methodsmentioning
confidence: 99%